Manufacturing method for electrode composite for all-solid-state lithium-ion battery

By combining electrode active materials, solid electrolyte raw materials, and carbon materials using mechanical energy, the method addresses the inefficiency of separate synthesis, resulting in high-productivity electrode assemblies with improved conductivity and capacity for all-solid-state lithium ion batteries.

JP7616715B2Active Publication Date: 2025-01-17NATIONAL INSTITUTE OF ADVANCED INDUSTRIAL SCIENCE & TECHNOLOGY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2023520869
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-05-12
Filing Date
2022-03-16
Publication Date
2025-01-17
Estimated Expiration
2042-03-16

AI Technical Summary

Technical Problem

Current methods for producing positive and negative electrode composites for all-solid-state lithium ion batteries are inefficient due to the lengthy synthesis of solid electrolytes, leading to poor mass productivity.

Method used

A method involving the combination of electrode active materials, solid electrolyte raw materials, and carbon materials using mechanical energy to synthesize a solid electrolyte directly in one step, enhancing productivity by eliminating the separate synthesis step.

Benefits of technology

This approach enables the production of electrode assemblies with improved mass productivity and battery characteristics, such as enhanced ionic conductivity and charge/discharge capacity, by ensuring the solid electrolyte is amorphous and uniformly dispersed.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616715000001
    Figure 0007616715000001
  • Figure 0007616715000002
    Figure 0007616715000002
  • Figure 0007616715000003
    Figure 0007616715000003
Patent Text Reader

Abstract

This method for producing an electrode composite body for all-solid-state lithium ion batteries complexes an electrode composite body starting material by means of a mechanical energy, the electrode composite body starting material containing an electrode active material, a solid electrolyte starting material, and a conductive material that is composed of a carbon material.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing an electrode composite for an all-solid-state lithium ion battery. This application claims priority based on Japanese Patent Application No. 2021-081219, filed on May 12, 2021, the contents of which are incorporated herein by reference. [Background technology]

[0002] Lithium-ion secondary batteries have a high energy density and are used in information-related devices such as personal computers and mobile phones. In recent years, development of high-output, high-capacity lithium-ion secondary batteries for electric or hybrid vehicles has been progressing.

[0003] However, current lithium-ion secondary batteries use flammable organic electrolytes, which means that they are prone to catching fire when they generate abnormal heat. In fact, there have been fires caused by lithium-ion secondary batteries in portable devices, and there is a strong demand for safety improvements.

[0004] By replacing the organic electrolyte in lithium-ion secondary batteries with an inorganic solid electrolyte, the risk of fire can be reduced, and for this reason, all-solid-state lithium-ion batteries are attracting attention.

[0005] Patent Document 1 discloses an all-solid-state battery including a positive electrode layer including a positive electrode active material and a first solid electrolyte, a negative electrode layer including a negative electrode active material and lithium hydride, and a solid electrolyte layer provided between the positive electrode layer and the negative electrode layer and including a second solid electrolyte, wherein the first solid electrolyte and the second solid electrolyte are glasses including an oxide represented by the general formula LixAyOz (A is at least one of S, B, C, P, Al, and Ti).

[0006] Patent Document 2 discloses an all-solid-state lithium secondary battery including a counter electrode layer, a negative electrode layer, and a sulfide glass-based electrolyte disposed between the counter electrode layer and the negative electrode layer, wherein the negative electrode layer is made of a mixture containing at least one high-capacity negative electrode material of Sn, Si, or Ge, and the sulfide glass-based electrolyte, a predetermined restraining force acts on both ends of the all-solid-state lithium secondary battery, and when the surface texture of the negative electrode layer is observed, no voids are observed in comparison with a 25 μm scale, and the surface texture is densified.

[0007] Patent Document 3 discloses a negative electrode mixture for an all-solid-state lithium ion secondary battery, the negative electrode mixture containing a negative electrode active material, a solid electrolyte, and a conductive material, the negative electrode active material containing at least one active material selected from the group consisting of metals capable of forming an alloy with Li and oxides of the metals, the solid electrolyte being a LiX-Li2S-P2S5 solid electrolyte (X is at least one halogen selected from the group consisting of F, Cl, Br, and I), and the value obtained by multiplying the volume ratio (%) of the conductive material when the volume of the negative electrode mixture is taken as 100 volume % by the bulk density of the solid electrolyte is 0.53 or more and 3.0 or less.

[0008] Patent Document 4 discloses a positive electrode for an all-solid-state secondary battery that includes a positive electrode active material represented by A2S·AX, where A is an alkali metal and X is selected from I, Br, Cl, F, BF4, BH4, SO4, BO3, PO4, O, Se, N, P, As, Sb, PF6, AsF6, ClO4, NO3, CO3, CF3SO3, CF3COO, N(SO2F)2, and N(CF3SO2)2. [Prior art documents] [Patent documents]

[0009] [Patent Document 1] Japanese Patent Publication No. 2020-64701 [Patent Document 2] Japanese Patent Publication No. 2020-161309 [Patent Document 3] Japanese Patent No. 6593381 [Patent Document 4] Japanese Patent No. 6529508 Summary of the Invention [Problem to be solved by the invention]

[0010] However, in the manufacturing methods of the positive electrode composite and the negative electrode composite disclosed in Patent Documents 1 to 4, a solid electrolyte is first synthesized, and then the positive electrode composite or the negative electrode composite is manufactured. In particular, since the synthesis of the solid electrolyte takes a long time, the manufacturing methods of the positive electrode composite and the negative electrode composite disclosed in Patent Documents 1 to 4 have a problem of poor mass productivity.

[0011] The present invention has been made in consideration of the above circumstances, and has an object to provide a method for producing an electrode composite for an all-solid-state lithium ion battery which is excellent in mass productivity. [Means for solving the problem]

[0012] In order to solve the above problems, the present invention proposes the following means. (1) A method for producing an electrode composite for an all-solid-state lithium ion battery according to one aspect of the present invention comprises compounding an electrode composite raw material, which includes an electrode active material, a solid electrolyte raw material, and a carbon material as a conductive material, by using mechanical energy.

[0013] (2) The method for producing an electrode composite for an all-solid-state lithium ion battery according to (1) above is characterized in that the specific surface area of ​​the carbon material is 10 m 2 / g or more.

[0014] (3) The method for producing an electrode composite for an all-solid-state lithium-ion battery according to the above (1) or (2) further comprises the step of: 2 / g or more.

[0015] (4) In the method for producing an electrode composite for an all-solid-state lithium ion battery according to any one of the above (1) to (3), the electrode active material may be a positive electrode active material.

[0016] (5) In the method for producing an electrode composite for an all-solid-state lithium-ion battery according to (4) above, the positive electrode active material may be a first Li2S.

[0017] (6) In the method for producing an electrode composite for an all-solid-state lithium-ion battery according to (5) above, the solid electrolyte raw material may be a sulfide solid electrolyte raw material containing a second Li2S and P2S5.

[0018] (7) In the method for producing an electrode composite for an all-solid-state lithium-ion battery described in (6) above, in the electrode composite raw material, a weight ratio of a sum of the first Li2S and the second Li2S, P2S5, and the carbon material may be 30-80:10-50:3-20.

[0019] (8) In the method for producing an electrode composite for an all-solid-state lithium ion battery according to (6) or (7) above, the electrode composite raw material may further contain a lithium salt.

[0020] (9) In the method for producing an electrode composite for an all-solid-state lithium-ion battery according to the above (8), the lithium salt may be at least one selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.

[0021] (10) In the method for producing an electrode composite for an all-solid-state lithium-ion battery according to (8) or (9) above, in the electrode composite raw material, a weight ratio of a sum of the first Li2S and the second Li2S, the P2S5, the carbon material, and the lithium salt may be 30-80:10-40:3-20:5-30.

[0022] (11) In the method for producing an electrode composite for an all-solid-state lithium-ion battery described in (5) above, the solid electrolyte raw material may include two or more selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.

[0023] (12) In the method for producing an electrode composite for an all-solid-state lithium ion battery described in (11) above, in the electrode composite raw material, a weight ratio of the first Li2S, the solid electrolyte raw material, and the carbon material may be 20-60:20-70:3-20.

[0024] (13) In the method for producing an electrode composite for an all-solid-state lithium ion battery according to any one of the above (1) to (3), the electrode active material may be a negative electrode active material.

[0025] (14) In the method for producing an electrode composite for an all-solid-state lithium ion battery according to (13) above, the negative electrode active material may be a Si-based active material made of one or more of Si and Si compounds.

[0026] (15) In the method for producing an electrode composite for an all-solid-state lithium ion battery according to (14) above, the Si-based active material may be Si.

[0027] (16) In the method for producing an electrode composite for an all-solid-state lithium-ion battery according to (14) or (15) above, the solid electrolyte raw material may be a sulfide solid electrolyte raw material containing Li2S and P2S5.

[0028] (17) In the method for producing an electrode composite for an all-solid-state lithium ion battery described in (16) above, in the electrode composite raw material, a weight ratio of the Si-based active material, Li2S, P2S5, and the carbon material may be 20-70:10-30:10-40:3-20.

[0029] (18) In the method for producing an electrode composite for an all-solid-state lithium ion battery according to (16) or (17) above, the electrode composite raw material may further contain a lithium salt.

[0030] (19) In the method for producing an electrode composite for an all-solid-state lithium-ion battery according to the above (18), the lithium salt may be at least one selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.

[0031] (20) In the method for producing an electrode composite for an all-solid-state lithium ion battery according to the above (18) or (19), a weight ratio of the Si-based active material, Li2S, P2S5, the carbon material, and the lithium salt in the electrode composite raw material may be 20-70:10-30:10-40:3-20:5-30.

[0032] (21) In the method for producing an electrode composite for an all-solid-state lithium-ion battery according to (14) or (15) above, the solid electrolyte raw material may contain at least two of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.

[0033] (22) In the method for producing an electrode composite for an all-solid-state lithium ion battery according to the above (21), a weight ratio of the Si-based active material, the solid electrolyte raw material, and the carbon material in the electrode composite raw material may be 10-60:20-80:3-20. Effect of the Invention

[0034] According to the above aspect of the present invention, it is possible to provide a method for producing an electrode composite for an all-solid-state lithium ion battery, which is excellent in mass productivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0035] The present inventors have found that an electrode composite for an all-solid-state lithium-ion battery can be produced in one step by compounding an electrode composite raw material containing an electrode active material, a solid electrolyte raw material, and a carbon material as a conductive material with mechanical energy, and have completed the present invention. In this specification, "compounding with mechanical energy" means synthesizing a solid electrolyte from a solid electrolyte raw material with mechanical energy, and dispersing an electrode active material and a carbon material in the synthesized solid electrolyte. Whether or not a solid electrolyte has been synthesized can be determined by the disappearance of the solid electrolyte raw material peak by XPS or the appearance of an exothermic peak other than the solid electrolyte raw material by DSC. It is preferable that the synthesized solid electrolyte is amorphous. Whether or not the solid electrolyte is amorphous can be confirmed by the disappearance of the diffraction peak of raw materials other than the active material by XRD. Hereinafter, each embodiment of the present invention will be described.

[0036] First Embodiment In the manufacturing method of the electrode composite for an all-solid-state lithium ion battery according to the first embodiment, an electrode composite raw material including a positive electrode active material as an electrode active material, a sulfide solid electrolyte raw material as a solid electrolyte raw material, and a carbon material is combined by mechanical energy. Each requirement will be described below.

[0037] [Electrode composite raw material] The electrode composite raw material used in the manufacturing method for an electrode composite for an all-solid-state lithium-ion battery according to the first embodiment includes a positive electrode active material, a sulfide solid electrolyte raw material, and a carbon material. By using the sulfide solid electrolyte raw material, which is a solid electrolyte raw material, the electrical conductivity of the electrode composite can be improved.

[0038] (Cathode active material) The positive electrode active material is not particularly limited as long as it does not lose its function as an active material when it is combined with other materials by mechanical energy. An example of the positive electrode active material is Li2S. L2S has a large theoretical capacity compared to conventional lithium transition metal oxides, and is therefore preferable because it dramatically improves the energy density. In addition, when the positive electrode active material is Li2S, since Li2S has a lithium source, the negative electrode active material does not need to have a lithium source. Therefore, by using Li2S as the positive electrode active material, it is not necessary to use unstable lithium metal or lithium metal alloy during production, and the manufacturing aspect is improved. In addition, by using Li2S, it is easy to uniformly disperse in the synthesized sulfide solid electrolyte while maintaining the characteristics of the active material. Therefore, Li2S (sometimes referred to as first Li2S) is preferable as the positive electrode active material.

[0039] (Sulfide solid electrolyte raw material) The sulfide solid electrolyte raw material is not particularly limited as long as at least a part of the sulfide solid electrolyte raw material becomes an amorphous sulfide solid electrolyte by compounding with mechanical energy. Examples of the sulfide solid electrolyte raw material include Li2S, P2S5, SiS2, GeS2, Al2S3, ZnS, As2S3, Sb2S3, WS2, and CuS. The sulfide solid electrolyte raw material preferably contains Li2S (hereinafter, sometimes referred to as second Li2S) and P2S5 (hereinafter, sometimes referred to as first P2S5). When the sulfide solid electrolyte raw material contains second Li2S and P2S5, a good sulfide solid electrolyte that is amorphous and has excellent deformability can be obtained by mechanical energy. When a sulfide solid electrolyte is synthesized from second Li2S and P2S5, the ratio of the first Li2S that functions as an electrode active material to the second Li2S used in the synthesis of the solid electrolyte is determined by the amount of P2S5.

[0040] (Carbon materials) The carbon material supplements the electric conductivity of the positive electrode active material. The carbon material is not particularly limited as long as it functions as a conductive material. The carbon material also has a function of promoting the synthesis of a solid electrolyte. Examples of the carbon material include acetylene black, carbon nanotubes, activated carbon, graphene, furnace black (for example, furnace black having a hollow shell structure), and carbon fiber. The carbon material may contain one or more of these. The furnace black having a hollow shell structure is a type of conductive furnace black, and has a hollow shell-like structure with a porosity of about 60 to 80%. Here, the "hollow shell structure" refers to a structure in which graphite crystals are thinly gathered together to form a particle-shaped outer shell, and the inside of the outer shell has voids. Examples of the furnace black having a hollow shell structure include Ketjen Black (manufactured by Lion Corporation).

[0041] When a carbon material with low conductivity (low-conductivity carbon material) is used, the electronic conductivity of the electrode composite can be improved by combining it with a carbon material with higher conductivity (high-conductivity carbon material). This can further improve the charge / discharge capacity of the electrode composite. The low-conductivity carbon material is activated carbon. The high-conductivity carbon material is one or more selected from the group consisting of acetylene black, ketjen black, carbon nanotubes, and graphene. The weight ratio of the low-conductivity carbon material to the high-conductivity carbon material is preferably low-conductivity carbon material:high-conductivity carbon material=10:0 to 5:5.

[0042] The specific surface area of ​​carbon materials is 10m 2 / g or more. More preferably, the specific surface area of ​​the carbon material is 100 m 2 More preferably, the specific surface area of ​​the carbon material is 1000 m 2 A particularly preferred specific surface area of ​​the carbon material is 1500 m 2 / g or more. The specific surface area is 10m 2If the specific surface area is less than 1 / g, the number of contact points between the positive electrode active material and the carbon material cannot be increased sufficiently, and therefore the effect of improving the charge / discharge capacity tends to be insufficient. 2 / g or less.

[0043] In this specification, the specific surface area of ​​a carbon material refers to the BET specific surface area determined by the Brenauer-Emmet-Telle (BET) method, specifically, the specific surface area determined using a nitrogen adsorption isotherm obtained by adsorbing nitrogen gas to a carbon material at liquid nitrogen temperature. As a measuring device for determining the BET specific surface area, for example, an automatic specific surface area / pore distribution measuring device (BELSORP-mini II, manufactured by BEL Japan Co., Ltd.) can be used.

[0044] (Lithium salts) The electrode composite raw material of the first embodiment may further contain a lithium salt in addition to the positive electrode active material, the sulfide solid electrolyte raw material, and the carbon material. The lithium salt has a function of improving the conductivity of the sulfide solid electrolyte and a function of improving the flexibility of the sulfide solid electrolyte. The lithium salt is not particularly limited as long as it has a function of improving the conductivity of the sulfide solid electrolyte or a function of improving the flexibility of the sulfide solid electrolyte. For example, the lithium salt is preferably one or more selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.

[0045] (Other ingredients) The electrode composite raw material of the first embodiment may further contain optional components such as a binder, a solvent, and an ion-conductive material.

[0046] "binder" The binder is not particularly limited, and may be a thermoplastic resin, a thermosetting resin, etc. Examples of the binder include polyethylene, polypropylene, polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), styrene butadiene rubber, tetrafluoroethylene-hexafluoroethylene copolymer, tetrafluoroethylene-hexafluoropropylene copolymer (FEP), tetrafluoroethylene-perfluoroalkyl vinyl ether copolymer (PFA), vinylidene fluoride-hexafluoropropylene copolymer, vinylidene fluoride-chlorotrifluoroethylene copolymer, ethylene-tetrafluoroethylene copolymer (ETFE resin), polychloro Examples of the binder include trifluoroethylene (PCTFE), vinylidene fluoride-pentafluoropropylene copolymer, propylene-tetrafluoroethylene copolymer, ethylene-chlorotrifluoroethylene copolymer (ECTFE), vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer, vinylidene fluoride-perfluoromethylvinyl ether-tetrafluoroethylene copolymer, ethylene-acrylic acid copolymer, polyacrylic acid, sodium polyacrylate, lithium polyacrylate, polymethacrylic acid, sodium polymethacrylate, lithium polymethacrylate, etc. These binders may be used alone or in combination of two or more.

[0047] When the electrode composite raw material contains a binder, its content is not particularly limited, but is preferably 0.01 to 10% by weight in the electrode composite raw material.

[0048] "solvent" By using an electrode composite obtained by mixing a solvent, it becomes easier to prepare an electrode composite layer. The solvent is removed by drying when preparing an electrode composite layer. The solvent is not particularly limited, but examples thereof include amine-based solvents such as N,N-dimethylaminopropylamine and diethylenetriamine, ether-based solvents such as tetrahydrofuran, ketone-based solvents such as methyl ethyl ketone, ester-based solvents such as methyl acetate, amide-based solvents such as dimethylacetamide and 1-methyl-2-pyrrolidone, and hydrocarbon-based solvents such as toluene, xylene, n-hexane, and cyclohexane. These solvents may be used alone or in combination of two or more.

[0049] When the electrode composite raw material is obtained by mixing the above-mentioned solvent, the content is not particularly limited, but is preferably 10 to 10,000 parts by weight per 100 parts by weight of the solid content of the electrode composite raw material.

[0050] "Ion-conducting materials" The electrode composite raw material may contain an ion-conductive material. The ion-conductive material is not particularly limited, but it is preferable that the lithium ion conductivity at room temperature is 10 -5 S / cm or more is preferable, and 10 -4 S / cm or more is more preferable. Examples of crystalline oxide solid electrolytes having such characteristics include lithium aluminum titanium phosphate (LATP), lithium aluminum germanium phosphate (LAGP), lithium lanthanum zirconium oxide (LLZ), lithium lanthanum titanium oxide (LLT), lithium germanium phosphorus sulfide (LGPS), lithium silicon sulfide (LSS), lithium phosphorus halide sulfide (LPSX), and lithium boron carbon hydride.

[0051] (weight ratio) In the first embodiment, when the positive electrode active material is the first Li2S and the sulfide solid electrolyte raw material is the second Li2S and P2S5, the weight ratio of the total of the first Li2S and the second Li2S, P2S5, and the carbon material in the electrode composite raw material (total of the first Li2S and the second Li2S: P2S5: carbon material) is preferably 30 to 80: 10 to 50: 3 to 20. When the weight ratio of the total of the first Li2S and the second Li2S, P2S5, and the carbon material in the electrode composite raw material is 30 to 80: 10 to 50: 3 to 20, the ion conductivity in the electrode composite and the contact points between the electrode active material, the solid electrolyte, and the carbon material can be sufficiently obtained, which is preferable because the battery characteristics are improved.

[0052] In the first embodiment, when the positive electrode active material is the first Li2S, the sulfide solid electrolyte raw material is the second Li2S and P2S5, and the electrode composite raw material further contains a lithium salt, the weight ratio of the total of the first Li2S and the second Li2S, P2S5, the carbon material, and the lithium salt in the electrode composite raw material (the total of the first Li2S and the second Li2S: P2S5: the carbon material: the lithium salt) is preferably 30 to 80: 10 to 40: 3 to 20: 5 to 30. When the weight ratio of the total of the first Li2S and the second Li2S, P2S5, the carbon material, and the lithium salt in the electrode composite raw material is 30 to 80: 10 to 40: 3 to 20: 5 to 30, the battery characteristics of the electrode composite are further improved, which is preferable.

[0053] [Composition through mechanical energy] Examples of the method of compounding the electrode composite raw material by mechanical energy include a method of compounding the electrode composite raw material using a planetary ball mill, a kneader, a planetary mixer, a vibration mill, a magnetic stirrer, or the like. For example, when using a planetary ball mill, the electrode composite raw material of the present disclosure is obtained by mixing the electrode composite raw material with zirconia balls at 370 rpm for 2 hours. The fact that the electrode composite raw material is compounded and a solid electrolyte is synthesized can be confirmed by X-ray photoelectron spectroscopy (XPS) showing the disappearance of the S 2p1 / 2 peak observed at about 165 eV corresponding to the crosslinking S of P2S5 used as the solid electrolyte raw material. The fact that the solid electrolyte is amorphous can be confirmed by the disappearance of diffraction peaks other than those of the electrode active material in powder X-ray diffraction (XRD) of the obtained electrode composite. By using a confirmation method such as XRD or XPS, the conditions during compounding can be appropriately adjusted.

[0054] In the manufacturing method of the electrode composite for all-solid-state lithium-ion batteries according to the first embodiment, the electrode composite raw material may be composited by mechanical energy and then subjected to a heat treatment. By performing the heat treatment, the contact interface between the electrode active material Li2S and the solid electrolyte raw material, the carbon material and / or the first lithium salt can be strengthened, and the interface resistance can be reduced. The heat treatment after the composite can be performed, for example, in an atmosphere of argon, nitrogen, air, or the like, at 80 to 250°C, preferably 100 to 200°C, for 1 second to 10 hours, without particular limitation. The heat treatment after the composite can be performed using a known heating device, and specifically, for example, a constant temperature dryer, a blower dryer, a reduced pressure dryer, an infrared dryer, an electric furnace, a gas replacement furnace, a hot plate, or the like.

[0055] [Electrode complex] The electrode composite manufactured by the manufacturing method for an electrode composite for an all-solid-state lithium-ion battery according to the first embodiment includes a positive electrode active material, a sulfide solid electrolyte, and a carbon material. The sulfide solid electrolyte is preferably amorphous. When the sulfide solid electrolyte is amorphous, it can be confirmed by powder X-ray diffraction (XRD) of the electrode composite that there is no diffraction peak other than that of the electrode active material. The generation of the sulfide solid electrolyte can be confirmed by X-ray photoelectron spectroscopy (XPS) of the electrode composite that the S 2p1 / 2 peak observed at about 165 eV corresponding to the crosslinking S of P2S5 used as the solid electrolyte raw material disappears. The XRD spectrum can be obtained by, for example, measuring with SmartLab II manufactured by RIGAKU Corporation in the 2θ range of 10 to 60°. The XPS spectrum can be measured by, for example, KRATOS Nova manufactured by KRATOS ANALYTICAL Corporation.

[0056] <Second embodiment> In the manufacturing method of the electrode composite for an all-solid-state lithium ion battery according to the second embodiment, an electrode composite raw material including a positive electrode active material, a solid electrolyte raw material, and a carbon material is composited by mechanical energy. Each requirement will be described below.

[0057] [Electrode composite raw material] The electrode composite raw material used in the manufacturing method for an electrode composite for an all-solid-state lithium ion battery according to the second embodiment includes a positive electrode active material, a solid electrolyte raw material, and a carbon material. By using the solid electrolyte raw material, the stability of the electrode composite can be improved.

[0058] (Cathode active material) The positive electrode active material is not particularly limited as long as it does not lose its function as an active material when it is combined with other materials by mechanical energy. An example of the positive electrode active material is L2S. L2S has a large theoretical capacity compared to conventional lithium transition metal oxides, and is therefore preferable because it dramatically improves the energy density. In addition, when the positive electrode active material is Li2S, since Li2S has a lithium source, the negative electrode active material does not need to have a lithium source. Therefore, by using Li2S as the positive electrode active material, it is not necessary to use unstable lithium metal or lithium metal alloy during production, and production aspects are improved. In addition, by using Li2S, it is easy to uniformly disperse in the synthesized solid electrolyte while maintaining the characteristics of the active material. Therefore, Li2S (first Li2S) is preferable as the positive electrode active material.

[0059] (Solid electrolyte raw material) The solid electrolyte raw material is not particularly limited as long as it can synthesize a solid electrolyte from the solid electrolyte raw material by compounding with mechanical energy. The solid electrolyte raw material is preferably two or more selected from the group consisting of lithium oxide (Li2O), lithium nitride, lithium fluoride, lithium chloride (LiCl), lithium bromide (LiBr), lithium iodide (LiI), lithium sulfate (Li2SO4), lithium carbonate (Li2CO3), lithium borate, lithium phosphate, lithium nitrate, lithium silicate (Li4SiO4), and lithium aluminate. The solid electrolyte raw material is particularly preferably Li2SO4, Li2CO3, LiCl, LiBr, LiI, Li2O, or Li4SiO4. By including these, it is possible to obtain a good solid electrolyte that is amorphous and has excellent deformability by mechanical energy.

[0060] (Carbon materials) The carbon material supplements the electrical conductivity of the positive electrode active material. The carbon material is not particularly limited as long as it functions as a conductive material. The carbon material also has a function of promoting the synthesis of a solid electrolyte. Examples of the carbon material include acetylene black, carbon nanotubes, activated carbon, graphene, furnace black (for example, furnace black having a hollow shell structure), carbon fiber, and the like. The carbon material may contain one or more of these. Examples of furnace black having a hollow shell structure include Ketjen Black (manufactured by Lion Corporation). When a low-conductivity carbon material is used, the electronic conductivity of the electrode composite can be improved by combining a low-conductivity carbon material with a high-conductivity carbon material. This further improves the charge / discharge capacity of the electrode composite. The low-conductivity carbon material is activated carbon. The high-conductivity carbon material is one or more selected from the group consisting of acetylene black, Ketjen black, carbon nanotubes, and graphene. The weight ratio of the low-conductivity carbon material to the high-conductivity carbon material is preferably low-conductivity carbon material:high-conductivity carbon material=10:0 to 5:5.

[0061] The specific surface area of ​​carbon materials is 10m 2 / g or more. More preferably, the specific surface area of ​​the carbon material is 100 m 2 More preferably, the specific surface area of ​​the carbon material is 1000 m 2 / g or more. More preferably, the specific surface area of ​​the carbon material is 1500 m 2 / g or more. The specific surface area is 10m 2 If the specific surface area is less than 1 / g, the number of contact points between the positive electrode active material and the carbon material cannot be increased sufficiently, and therefore the effect of improving the charge / discharge capacity tends to be insufficient. 2 / g or less.

[0062] (Other ingredients) The electrode composite raw material of the second embodiment may further contain optional components such as a binder, a solvent, and an ion-conductive material.

[0063] (weight ratio) In the second embodiment, when the positive electrode active material is the first Li2S and the solid electrolyte raw material is two or more selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate, the weight ratio of the first Li2S, the solid electrolyte raw material, and the carbon material (first Li2S: solid electrolyte raw material: carbon material) is preferably 20-60:20-70:3-20. When the weight ratio of the solid electrolyte raw material and the carbon material in the electrode composite raw material is 20-60:20-70:3-20, the ion conductivity in the electrode composite and the contact points between the active material, the solid electrolyte, and the carbon material can be sufficiently obtained, so that the battery characteristics are improved, which is preferable. By compounding two or more selected from the above group with mechanical energy, at least a part of the solid electrolyte raw material becomes a solid electrolyte.

[0064] [Composition through mechanical energy] The method of compounding the electrode composite raw materials by mechanical energy may be the same as that of the first embodiment. The fact that the electrode composite raw materials are compounded and a solid electrolyte is synthesized can be confirmed, for example, by performing DSC measurement of the electrode composite and confirming the position of the exothermic peak. In addition, the fact that the solid electrolyte is amorphous can be confirmed by performing XRD measurement of the obtained electrode composite and the disappearance of the diffraction peaks of the solid electrolyte raw materials other than the electrode active material. The conditions during compounding can be appropriately adjusted using confirmation methods such as XRD and DSC.

[0065] In the method for producing an electrode composite for an all-solid-state lithium-ion battery according to the second embodiment, a heat treatment may be carried out after the electrode composite raw material is composited by mechanical energy. The heat treatment may be carried out in the same manner as in the first embodiment.

[0066] [Electrode complex] The electrode composite produced by the method for producing an electrode composite for an all-solid-state lithium ion battery according to the second embodiment includes a positive electrode active material, a solid electrolyte, and a carbon material. The solid electrolyte is preferably amorphous.

[0067] When the solid electrolyte of the electrode composite is amorphous, for example, in the XRD spectrum obtained by measurement in the 2θ range of 10 to 60° using a SmartLab II manufactured by RIGAKU Corporation, the diffraction peak of the solid electrolyte raw material disappears. In addition, the solid electrolyte has an exothermic peak at 400°C or less, different from that of the solid electrolyte raw material, in a curve (DSC curve) obtained by differential scanning calorimetry (DSC) measurement. The DSC curve is obtained by installing a differential scanning calorimeter (for example, DSC6200 manufactured by Seiko Instruments Inc.) and performing measurement in the temperature range of 50°C to 500°C and at a heating rate of 5°C / min.

[0068] <Third embodiment> In the manufacturing method of the electrode composite for an all-solid-state lithium ion battery according to the third embodiment, an electrode composite raw material including a negative electrode active material, a sulfide solid electrolyte raw material, and a carbon material is composited by mechanical energy. Each requirement will be described below.

[0069] [Electrode composite raw material] The electrode composite raw material used in the manufacturing method for an electrode composite for an all-solid-state lithium ion battery according to the third embodiment includes a negative electrode active material, a sulfide solid electrolyte raw material, and a carbon material. By using the sulfide solid electrolyte raw material, the electrical conductivity of the electrode composite can be improved.

[0070] (Negative electrode active material) The negative electrode active material is not particularly limited as long as it does not lose its function as an active material when it is combined with other materials by mechanical energy. The negative electrode active material is, for example, a Si-based active material consisting of one type of Si and a Si compound. If the negative electrode active material is a Si-based active material, it can be uniformly dispersed in the sulfide solid electrolyte when the electrode composite raw material is combined by mechanical energy. Examples of the Si compound include SiO and LiSi. In particular, as the Si-based active material, Si is preferable because it has a very large theoretical capacity compared to conventional graphite.

[0071] (Sulfide solid electrolyte raw material) The sulfide solid electrolyte raw material is not particularly limited as long as it can be synthesized into a sulfide solid electrolyte by compounding with mechanical energy. Examples of the sulfide solid electrolyte raw material include Li2S, P2S5, SiS2, GeS 2、 Examples of the sulfide solid electrolyte raw material include Al2S3, ZnS, As2S3, Sb2S3, WS2, and CuS. The sulfide solid electrolyte raw material preferably contains Li2S and P2S5. By containing Li2S and P2S5 in the sulfide solid electrolyte raw material, it is possible to obtain a good sulfide solid electrolyte that is amorphous and has excellent deformability by mechanical energy.

[0072] (Carbon materials) The carbon material supplements the electrical conductivity of the negative electrode active material. The carbon material is not particularly limited as long as it functions as a conductive material. The carbon material also has a function of promoting the synthesis of a solid electrolyte. Examples of the carbon material include acetylene black, carbon nanotubes, activated carbon, graphene, furnace black (for example, furnace black having a hollow shell structure), carbon fiber, and the like. The carbon material may contain one or more of these. Examples of furnace black having a hollow shell structure include Ketjen Black (manufactured by Lion Corporation). When a low-conductivity carbon material is used, the electronic conductivity of the electrode composite can be improved by combining a low-conductivity carbon material with a high-conductivity carbon material. This further improves the charge / discharge capacity of the electrode composite. The low-conductivity carbon material is activated carbon. The high-conductivity carbon material is one or more selected from the group consisting of acetylene black, Ketjen black, carbon nanotubes, and graphene. The weight ratio of the low-conductivity carbon material to the high-conductivity carbon material is preferably low-conductivity carbon material:high-conductivity carbon material=10:0 to 5:5.

[0073] The specific surface area of ​​carbon materials is 10m 2 / g or more. More preferably, the specific surface area of ​​the carbon material is 100 m 2 More preferably, the specific surface area of ​​the carbon material is 1000 m 2 A particularly preferred specific surface area of ​​the carbon material is 1500 m 2 / g or more. The specific surface area is 10m 2 If the specific surface area is less than 1 / g, the number of contact points between the negative electrode active material and the carbon material cannot be increased sufficiently, and therefore the effect of improving the charge / discharge capacity tends to be insufficient. 2 / g or less.

[0074] (Lithium salts) The electrode composite raw material of the third embodiment may further contain a lithium salt (lithium salt) in addition to the negative electrode active material, the sulfide solid electrolyte raw material, and the carbon material. The lithium salt has a function of improving the conductivity of the sulfide solid electrolyte and a function of improving the flexibility of the sulfide solid electrolyte. The lithium salt is not particularly limited as long as it has a function of improving the conductivity of the sulfide solid electrolyte or a function of improving the flexibility of the sulfide solid electrolyte. For example, the lithium salt is preferably one or more selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.

[0075] (Other ingredients) The electrode composite raw material of the third embodiment may further contain optional components such as a binder, a solvent, and an ion-conductive material.

[0076] (weight ratio) In the third embodiment, when the negative electrode active material is a Si-based active material and the sulfide solid electrolyte raw material is Li2S and P2S5, the weight ratio of the Si-based active material, Li2S, P2S5, and carbon material in the electrode composite raw material (Si-based active material: Li2S: P2S5: carbon material) is preferably 20-70: 10-30: 10-40: 3-20. When the weight ratio of the Si-based active material, Li2S, P2S5, and carbon material in the electrode composite raw material is 20-70: 10-30: 10-40: 3-20, the ion conductivity in the electrode composite and the contact points between the active material, the solid electrolyte, and the carbon material can be sufficiently obtained, which is preferable because the battery characteristics are improved.

[0077] In the third embodiment, when the negative electrode active material is a Si-based active material, the sulfide solid electrolyte raw material is Li2S and P2S5, and the electrode composite raw material further contains a lithium salt, the weight ratio of the Si-based active material, Li2S, P2S5, carbon material, and lithium salt in the electrode composite raw material (Si-based active material: Li2S: P2S5: carbon material: lithium salt) is preferably 20-70: 10-30: 10-40: 3-20: 5-30. When the weight ratio of the Si-based active material, Li2S, P2S5, carbon material, and lithium salt in the electrode composite raw material is 20-70: 10-30: 10-40: 3-20: 5-30, the battery characteristics of the electrode composite are further improved, which is preferable.

[0078] [Composition through mechanical energy] The electrode composite raw material can be composited by mechanical energy in the same manner as in the first embodiment. The synthesis of the sulfide solid electrolyte can be confirmed in the same manner as in the first embodiment.

[0079] In the manufacturing method of the electrode composite for an all-solid-state lithium ion battery according to the third embodiment, the electrode composite raw material may be composited by mechanical energy, and then a heat treatment may be performed under the same conditions as those in the first embodiment.

[0080] [Electrode complex] The electrode composite produced by the method for producing an electrode composite for an all-solid-state lithium ion battery according to the third embodiment includes a negative electrode active material, a sulfide solid electrolyte, and a carbon material. It is preferable that at least a part of the sulfide solid electrolyte is amorphous.

[0081] Whether or not the sulfide solid electrolyte is generated can be confirmed by XPS, as in the first embodiment. Whether or not the sulfide solid electrolyte is amorphous can be confirmed by XRD, as in the first embodiment.

[0082] <Fourth embodiment> In the manufacturing method of the electrode composite for an all-solid-state lithium ion battery according to the fourth embodiment, an electrode composite raw material including a negative electrode active material as an electrode active material, a solid electrolyte raw material, and a carbon material is composited by mechanical energy. Each requirement will be described below.

[0083] [Electrode composite raw material] The electrode composite raw material used in the manufacturing method for an electrode composite for an all-solid-state lithium ion battery according to the fourth embodiment includes a negative electrode active material, a solid electrolyte raw material, and a carbon material. By using the solid electrolyte raw material, the stability of the electrode composite can be improved.

[0084] The negative electrode active material is not particularly limited as long as it does not lose its function when it is combined with other materials by mechanical energy. The negative electrode active material is, for example, a Si-based active material consisting of one of Si and Si compounds. If the negative electrode active material is a Si-based active material, it can be uniformly dispersed in the solid electrolyte when the electrode composite raw material is combined by mechanical energy. Examples of the Si compound include SiO and LiSi. In particular, as the Si-based active material, Si is particularly preferred because it has a very large theoretical capacity compared to conventional graphite.

[0085] (Solid electrolyte raw material) The solid electrolyte raw material is not particularly limited as long as it can synthesize a solid electrolyte from the solid electrolyte raw material by compounding with mechanical energy. The solid electrolyte raw material is preferably two or more selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate (Li2SO4), lithium carbonate (Li2CO3), lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate. The solid electrolyte raw material is particularly preferably Li2SO4, Li2CO3, LiCl, LiBr, LiI, Li2O, or Li4SiO4. By including these, it is possible to obtain a good solid electrolyte that is amorphous and has excellent deformability by mechanical energy.

[0086] (Carbon materials) The carbon material supplements the electrical conductivity of the negative electrode active material. The carbon material is not particularly limited as long as it functions as a conductive material. The carbon material also has a function of promoting the synthesis of a solid electrolyte. Examples of the carbon material include acetylene black, carbon nanotubes, activated carbon, graphene, furnace black (for example, furnace black having a hollow shell structure), carbon fiber, and the like. The carbon material may contain one or more of these. Examples of furnace black having a hollow shell structure include Ketjen Black (manufactured by Lion Corporation). When a low-conductivity carbon material is used, the electronic conductivity of the electrode composite can be improved by combining a low-conductivity carbon material with a high-conductivity carbon material. This further improves the charge / discharge capacity of the electrode composite. The low-conductivity carbon material is activated carbon. The high-conductivity carbon material is one or more selected from the group consisting of acetylene black, Ketjen black, carbon nanotubes, and graphene. The weight ratio of the low-conductivity carbon material to the high-conductivity carbon material is preferably low-conductivity carbon material:high-conductivity carbon material=10:0 to 5:5.

[0087] The specific surface area of ​​carbon materials is 10m 2 / g or more. More preferably, the specific surface area of ​​the carbon material is 100 m 2 More preferably, the specific surface area of ​​the carbon material is 1000 m 2 A particularly preferred specific surface area of ​​the carbon material is 1500 m 2 / g or more. The specific surface area is 10m 2 If the specific surface area is less than 1 / g, the number of contact points between the negative electrode active material and the carbon material cannot be increased sufficiently, and therefore the effect of improving the charge / discharge capacity tends to be insufficient. 2 / g or less.

[0088] (Other ingredients) The electrode composite raw material of the fourth embodiment may further contain optional components such as a binder, a solvent, and an ion-conductive material.

[0089] (weight ratio) In the fourth embodiment, when the negative electrode active material is a Si-based active material and the solid electrolyte raw material is two or more selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate, the weight ratio of the Si-based active material, the solid electrolyte raw material, and the carbon material (Si-based active material: solid electrolyte raw material: carbon material) is preferably 10 to 60: 20 to 80: 3 to 20. When the weight ratio of the Si-based active material, the solid electrolyte raw material, and the carbon material in the electrode composite raw material is 10 to 60: 20 to 80: 3 to 20, the ion conductivity in the electrode composite and the contact points between the active material, the solid electrolyte, and the carbon material can be sufficiently obtained, which is preferable because the battery characteristics are improved.

[0090] [Composition through mechanical energy] The method of compounding the electrode composite raw materials by mechanical energy may be the same as that of the first embodiment. The fact that the electrode composite raw materials are compounded and a solid electrolyte is synthesized can be confirmed, for example, by performing DSC measurement of the electrode composite and confirming the position of the exothermic peak. In addition, the fact that the solid electrolyte is amorphous can be confirmed by performing XRD measurement of the obtained electrode composite and the disappearance of the diffraction peaks of the solid electrolyte raw materials other than the electrode active material. The conditions during compounding can be appropriately adjusted using confirmation methods such as XRD and DSC.

[0091] In the manufacturing method of the electrode composite for an all-solid-state lithium ion battery according to the fourth embodiment, the electrode composite raw material may be composited by mechanical energy, and then a heat treatment may be performed. The heat treatment may be performed in the same manner as in the first embodiment.

[0092] [Electrode complex] The electrode composite manufactured by the manufacturing method of the electrode composite for an all-solid-state lithium ion battery according to the fourth embodiment includes a negative electrode active material, a solid electrolyte, and a carbon material. It is preferable that a part of the solid electrolyte is amorphous.

[0093] Whether the solid electrolyte is amorphous or not can be confirmed by XRD or DSC, similarly to the second embodiment.

[0094] The manufacturing method of the electrode composite for an all-solid-state lithium ion battery according to the present disclosure has been described above in detail. In addition, the components in the above-described embodiment may be appropriately replaced with known components without departing from the spirit of the present invention. EXAMPLES

[0095] Next, an embodiment of the present invention will be described, but the conditions in the embodiment are merely an example of conditions adopted to confirm the feasibility and effects of the present invention, and the present invention is not limited to this example of conditions. Various conditions can be adopted in the present invention as long as they do not deviate from the gist of the present invention and achieve the object of the present invention.

[0096] (Cathode Composite 1) The electrode composite raw materials were Li2S (Mitsuwa Chemical Industry Co., Ltd.), P2S5 (Sigma-Aldrich Co., Ltd.), and activated carbon A (MSC30, Kansai Thermal Chemical Industry Co., Ltd., specific surface area 3000 m 2 Li2S: 114 mg, P2S5: 66 mg, and activated carbon: 20 mg were weighed out so that the weight ratio of the electrode composite raw material was 57:33:10 (114 mg / g). The weighed electrode composite raw material was placed in a 45 ml pot together with about 40 g of 5 mm zirconia balls using a planetary ball mill (Frilsch Premium Line P-7), and mixed for 2 hours at a revolution speed of 370 rpm to obtain positive electrode composite 1.

[0097] (Cathode Composite 2) Positive electrode composite 2 was obtained by carrying out the same process as positive electrode composite 1, except that 100 mg of Li2S, 60 mg of P2S5, 20 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:LiI (manufactured by Sigma-Aldrich):activated carbon A was 50:30:10:10.

[0098] (Cathode Composite 3) Positive electrode composite 3 was obtained by carrying out the same treatment as for positive electrode composite 1, except that 130 mg of Li2S, 50 mg of P2S5, and 20 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:activated carbon A was 65:25:10.

[0099] (Cathode Composite 4) Positive electrode composite 4 was obtained by carrying out the same process as for positive electrode composite 1, except that 140 mg of Li2S, 40 mg of P2S5, and 20 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:activated carbon A was 70:20:10.

[0100] (Cathode Composite 5) Positive electrode composite 5 was obtained by carrying out the same process as positive electrode composite 1, except that 120 mg of Li2S, 40 mg of P2S5, 20 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:LiI:activated carbon A was 60:20:10:10.

[0101] (Cathode Composite 6) Positive electrode composite 6 was obtained by carrying out the same process as positive electrode composite 1, except that 130 mg of Li2S, 40 mg of P2S5, 10 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:LiI:activated carbon A was 65:20:5:10.

[0102] (Cathode Composite 7) Positive electrode composite 7 was obtained by carrying out the same treatment as for positive electrode composite 1, except that 120 mg of Li2S, 62 mg of P2S5, and 18 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:activated carbon A was 60:31:9.

[0103] (Cathode Composite 8) Positive electrode composite 8 was obtained by the same treatment as for positive electrode composite 1, except that 120 mg of Li2S, 58 mg of P2S5, and 22 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:activated carbon A was 60:29:11.

[0104] (Cathode Composite 9) Positive electrode composite 9 was obtained by carrying out the same treatment as for positive electrode composite 1, except that 120 mg of Li2S, 66 mg of P2S5, and 14 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:activated carbon A was 60:33:7.

[0105] (Cathode Composite 10) Positive electrode composite 10 was obtained by carrying out the same process as positive electrode composite 1, except that 120 mg of Li2S, 20 mg of P2S5, 50 mg of LiI, and 10 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:LiI:activated carbon A was 60:10:25:5.

[0106] (Cathode Composite 11) Positive electrode composite 11 was obtained by the same treatment as positive electrode composite 1, except that 120 mg of Li2S, 20 mg of P2S5, 40 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:LiI:activated carbon A was 60:10:20:10.

[0107] (Cathode Composite 12) Instead of activated carbon A, activated carbon B (MSA20, manufactured by Kansai Thermochemical Co., Ltd., specific surface area 2500 m 2 A positive electrode composite 12 was obtained by carrying out the same treatment as in the positive electrode composite 10, except that a positive electrode composite 12 containing 10% by weight of 1 / g was used.

[0108] (Cathode Composite 13) Instead of activated carbon A, Ketjen black (EC600JD, Lion Corporation, specific surface area 1200 m 2 A positive electrode composite 13 was obtained by carrying out the same treatment as in the positive electrode composite 10, except that a positive electrode composite 13 containing 1,2-dichlorobenzene and 1,2-dichlorobenzene was used instead.

[0109] (Cathode Composite 14) Instead of activated carbon A, acetylene black (Li-100, manufactured by DENKA, specific surface area 100 m 2 A positive electrode composite 14 was obtained by carrying out the same treatment as in positive electrode composite 10, except that a positive electrode composite 14 containing 100% cellulose ester (C10 / g) was used.

[0110] (Cathode Composite 15) Positive electrode composite 15 was obtained by carrying out the same treatment as for positive electrode composite 1, except that 120 mg of Li2S, 60 mg of P2S5, and 20 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:activated carbon B was 60:30:10.

[0111] (Cathode Composite 16) Positive electrode composite 16 was obtained by carrying out the same treatment as for positive electrode composite 11, except that LiBr (manufactured by Sigma-Aldrich) was used instead of LiI.

[0112] (Cathode Composite 17) Positive electrode composite 17 was obtained by the same treatment as positive electrode composite 1, except that 100 mg of Li2S, 20 mg of P2S5, 60 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Li2S:P2S5:LiI:activated carbon A was 50:10:30:10.

[0113] (Cathode Composite 18) Positive electrode composite 18 was obtained by the same process as positive electrode composite 1, except that 60 mg of Li2S, 63 mg of Li2SO4, 29 mg of Li2CO3, 28 mg of LiBr, and 20 mg of activated carbon were used so that the weight ratio of Li2S:Li2SO4:Li2CO3:LiBr:activated carbon A was 30:31.5:14.5:14:10.

[0114] (Cathode Composite 19) Positive electrode composite 19 was obtained by carrying out the same treatment as in Positive electrode composite 18, except that the ball mill treatment time was changed from 2 hours to 8 hours.

[0115] (Cathode Composite 20) Positive electrode composite 20 was obtained by the same process as positive electrode composite 19, except that 60 mg of Li2S, 52 mg of Li2SO4, 23 mg of Li2CO3, 45 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Li2S:Li2SO4:Li2CO3:LiI:activated carbon A was 30:26:11.5:22.5:10.

[0116] (Cathode Composite 21) Positive electrode composite 21 was obtained by the same process as positive electrode composite 19, except that 60 mg of Li2S, 37 mg of Li2O, 83 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Li2S:Li2O:LiI:activated carbon A was 30:18.5:41.5:10.

[0117] (Cathode Composite 22) Positive electrode composite 22 was obtained by the same process as positive electrode composite 19, except that 60 mg of Li2S, 58 mg of Li2SO4, 11 mg of Li2O, 51 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Li2S:Li2SO4:Li2O:LiI:activated carbon A was 30:29:5.5:25.5:10.

[0118] (Comparative Positive Electrode Composite 1) A comparative positive electrode composite 1 was obtained by treating 80Li2S-20P2S5 in a ball mill at 500 rpm for 10 hours using a solid electrolyte 1, and treating it in the same manner as in positive electrode composite 1, except that 100 mg of Li2S, 80 mg of solid electrolyte 1, and 20 mg of activated carbon were used so that the weight ratio of Li2S:solid electrolyte 1:activated carbon was 50:40:10.

[0119] (Comparative Positive Electrode Composite 2) Comparative positive electrode composite 2 was obtained by carrying out the same process as comparative positive electrode composite 1, except that solid electrolyte 2 obtained by treating 60Li2S-40P2S5 in a ball mill at 500 rpm for 10 hours was used instead of solid electrolyte 1.

[0120] (Comparative Positive Electrode Composite 3) A solid electrolyte 3 obtained by treating 45Li2SO4-30Li2CO3-25LiBr in a ball mill at 370 rpm for 60 hours was used, and a comparative positive electrode composite 3 was obtained by carrying out the same treatment as in comparative positive electrode composite 1, except that 60 mg of Li2S, 120 mg of solid electrolyte 3, and 20 mg of activated carbon were used so that the weight ratio of Li2S:solid electrolyte 3:activated carbon was 30:60:10.

[0121] (Comparative Positive Electrode Composite 4) Comparative positive electrode composite 4 was obtained by carrying out the same process as in comparative positive electrode composite 3, except that solid electrolyte 4 obtained by treating 45Li2SO4-30Li2CO3-30LiI in a ball mill at 370 rpm for 60 hours was used instead of solid electrolyte 3.

[0122] (Negative electrode composite 1) A negative electrode composite 1 was obtained by carrying out the same process as for positive electrode composite 1, except that 100 mg of Si, 18 mg of Li2S, 28 mg of P2S5, 34 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Si (manufactured by Nilaco Corporation, purity 99.999%):Li2S:P2S5:LiI:activated carbon A was 50:9:14:17:10.

[0123] (Anode composite 2) Negative electrode composite 2 was obtained by carrying out the same process as positive electrode composite 1, except that 100 mg of Si, 17 mg of Li2S, 28 mg of P2S5, 33 mg of LiI, and 22 mg of activated carbon were used so that the weight ratio of Si:Li2S:P2S5:LiI:activated carbon A was 50:8.5:14:16.5:11.

[0124] (Anode composite 3) Negative electrode composite 3 was obtained by carrying out the same process as positive electrode composite 1, except that 100 mg of Si, 18 mg of Li2S, 29 mg of P2S5, 35 mg of LiI, and 18 mg of activated carbon were used so that the weight ratio of Si:Li2S:P2S5:LiI:activated carbon A was 50:9:14.5:17.5:9.

[0125] (Anode composite 4) A negative electrode composite 4 was obtained by carrying out the same treatment as in the positive electrode composite 1, except that the activated carbon B was used instead of the activated carbon A.

[0126] (Negative electrode complex 5) A negative electrode composite 5 was obtained by carrying out the same treatment as in the positive electrode composite 1, except that Ketjen black was used instead of the activated carbon A.

[0127] (Anode composite 6) A negative electrode composite 6 was obtained by carrying out the same treatment as in the positive electrode composite 1, except that acetylene black was used instead of activated carbon A.

[0128] (Negative electrode complex 7) Negative electrode composite 7 was obtained by carrying out the same process as positive electrode composite 1, except that 100 mg of Si, 15 mg of Li2S, 25 mg of P2S5, 30 mg of LiI, and 30 mg of activated carbon were used so that the weight ratio of Si:Li2S:P2S5:LiI:activated carbon B was 50:7.5:12.5:15:15.

[0129] (Anode composite 8) Negative electrode composite 8 was obtained by carrying out the same process as positive electrode composite 1, except that 100 mg of Si, 13 mg of Li2S, 21 mg of P2S5, 26 mg of LiI, and 40 mg of activated carbon B were used so that the weight ratio of Si:Li2S:P2S5:LiI:activated carbon B was 50:6.5:10.5:13:20.

[0130] (Negative electrode composite 9) Negative electrode composite 9 was obtained by carrying out the same process as positive electrode composite 1, except that 100 mg of Si, 31 mg of Li2S, 49 mg of P2S5, and 20 mg of activated carbon were used so that the weight ratio of Si:Li2S:P2S5:activated carbon A was 50:15.5:24.5:10.

[0131] (Negative electrode composite 10) A negative electrode composite 10 was obtained by carrying out the same process as for positive electrode composite 19, except that 60 mg of Si, 52 mg of Li2SO4, 23 mg of Li2CO3, 45 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Si:Li2SO4:Li2CO3:LiI:activated carbon A was 30:26:11.5:22.5:10.

[0132] (Negative electrode composite 11) A negative electrode composite 11 was obtained by carrying out the same process as for the positive electrode composite 19, except that 60 mg of Si, 37 mg of Li2O, 83 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Si:Li2O:LiI:activated carbon A was 30:18.5:41.5:10.

[0133] (Negative electrode composite 12) A negative electrode composite 12 was obtained by carrying out the same process as for positive electrode composite 19, except that 60 mg of Si, 75 mg of Li2SO4, 45 mg of LiI, and 20 mg of activated carbon were used so that the weight ratio of Si:Li2SO4:LiI:activated carbon A was 30:37.5:22.5:10.

[0134] (Comparative negative electrode composite 1) A comparative negative electrode composite 1 was obtained by treating 3Li2S-1P2S5-2LiI in a ball mill at 500 rpm for 10 hours using solid electrolyte 5, and treating it in the same manner as in positive electrode composite 1, except that 100 mg of Si, 80 mg of solid electrolyte 5, and 20 mg of activated carbon were used so that the weight ratio of Si:solid electrolyte 5:activated carbon A was 50:40:10.

[0135] (Comparative negative electrode composite 2) Comparative negative electrode composite 2 was obtained by carrying out the same process as in comparative negative electrode composite 1, except that solid electrolyte 6 obtained by treating 75Li2S-25P2S5 in a ball mill at 500 rpm for 10 hours was used instead of solid electrolyte 5.

[0136] (Comparative negative electrode composite 3) Comparative negative electrode composite 3 was obtained by carrying out the same process as in comparative negative electrode composite 1, except that solid electrolyte 7 obtained by treating 42Li2SO4-28Li2CO3-30LiI in a ball mill at 370 rpm for 60 hours was used instead of solid electrolyte 5.

[0137] (Li2S positive electrode half-cell preparation condition 1: positive electrode composites 1-17, comparative positive electrode composites 1-2) In an argon gas atmosphere glove box, a cylindrical jig (10 mmΦ, 10 mm height) made of SUS304 was inserted as a negative electrode current collector from the bottom of a cylindrical tube jig made of polycarbonate (inner diameter 10 mmΦ, outer diameter 23 mmΦ, height 20 mm). Next, 80 mg of solid electrolyte (E-1) (composite 1 obtained by firing 5Li2S-GeS2-P2S5 at 510°C for 8 hours and composite 2 obtained by treating 80Li2S-20P2S5 in a ball mill at 500 rpm for 10 hours, mixed in a weight ratio of 90:10) was placed from the top of the cylindrical tube jig made of polycarbonate. Furthermore, a cylindrical jig (10 mmΦ, 15 mm height) made of SUS304 was inserted from the top of the cylindrical tube jig made of polycarbonate as a positive electrode collector, and the solid electrolyte (E-1) was sandwiched between the cylindrical tube jig and pressed at a pressure of 80 MPa for 3 minutes to form a solid electrolyte layer with a diameter of 10 mmΦ and a thickness of about 0.6 mm. Next, the cylindrical jig made of SUS304 (positive electrode collector) inserted from the top was temporarily removed, and 7.5 mg of the positive electrode composite was placed on the solid electrolyte layer in the cylindrical tube made of polycarbonate. After that, a cylindrical jig made of SUS304 (positive electrode collector) was inserted from the top again and pressed at a pressure of 200 MPa for 3 minutes to form a positive electrode composite layer with a diameter of 10 mmΦ and a thickness of about 0.1 mm. Next, the SUS304 cylindrical jig (negative electrode current collector) inserted from the bottom was removed, and a 0.20 mm thick lithium sheet (manufactured by Honjo Metals) punched to a diameter of 8 mmΦ with a hole punch and a 0.3 mm thick indium sheet (manufactured by Furuuchi Chemicals) punched to a diameter of 9 mmΦ with a hole punch were stacked and inserted from the bottom of the polycarbonate cylindrical tube jig. A SUS304 cylindrical jig (negative electrode current collector) was inserted from the bottom again and pressed at a pressure of 80 MPa for 3 minutes to form a lithium-indium alloy negative electrode. In this way, an all-solid-state lithium ion battery was produced in which, from the bottom, a negative electrode current collector, a lithium-indium alloy negative electrode, a solid electrolyte layer, a positive electrode composite layer, and a positive electrode current collector were stacked. This was sealed to form a battery for evaluating the positive electrode composite.

[0138] (Li2S positive electrode half-cell preparation condition 2: positive electrode composites 18-22, comparative positive electrode composites 3-4) In an argon gas atmosphere glove box, a cylindrical jig made of SKD11 (10 mmΦ, 10 mm height) was inserted as a negative electrode current collector from the bottom of a ceramic cylindrical tube jig (inner diameter 10 mmΦ, outer diameter 23 mmΦ, height 20 mm). Next, 80 mg of solid electrolyte (E-1) (composite 1 obtained by firing 5Li2S-GeS2-P2S5 at 510℃ for 8 hours and composite 2 obtained by treating 80Li2S-20P2S5 in a ball mill at 500 rpm for 10 hours, mixed in a weight ratio of 90:10) was placed from the top of the ceramic cylindrical tube jig. Furthermore, a cylindrical jig (10 mmΦ, 15 mm height) made of SKD11 was inserted from the top of the ceramic cylindrical tube jig as a positive electrode current collector, and the solid electrolyte (E-1) was sandwiched between the cylindrical jig and pressed for 3 minutes at a pressure of 80 MPa to form a solid electrolyte layer with a diameter of 10 mmΦ and a thickness of approximately 0.6 mm. Next, the cylindrical jig made of SKD11 (positive electrode current collector) inserted from the top was temporarily removed, and 10 mg of the positive electrode composite was placed on top of the solid electrolyte layer in the ceramic cylindrical tube. After that, the cylindrical jig made of SKD11 (positive electrode current collector) was inserted from the top again and pressed for 3 minutes at a pressure of 720 MPa to form a positive electrode composite layer with a diameter of 10 mmΦ and a thickness of approximately 0.1 mm. Next, the cylindrical jig (negative electrode current collector) made of SKD11 inserted from the bottom was removed, and a lithium sheet (manufactured by Honjo Metals) with a thickness of 0.20 mm was punched out to a diameter of 8 mmΦ with a hole punch as a negative electrode, and an indium sheet (manufactured by Furuuchi Chemical Co., Ltd.) with a thickness of 0.3 mm was punched out to a diameter of 9 mmΦ with a hole punch, and these were stacked and inserted from the bottom of the ceramic cylindrical tube jig. The cylindrical jig (negative electrode current collector) made of SKD11 was inserted again from the bottom, and pressed for 3 minutes at a pressure of 80 MPa to form a lithium-indium alloy negative electrode. In this way, an all-solid-state lithium ion battery was produced in which, from the bottom, a negative electrode current collector, a lithium-indium alloy negative electrode, a solid electrolyte layer, a positive electrode composite layer, and a positive electrode current collector were laminated. This was sealed to form a battery for evaluating the positive electrode composite.

[0139] (Si negative electrode half-cell preparation condition 1: negative electrode composites 1-9, comparative negative electrode composites 1-2) In an argon gas atmosphere glove box, a cylindrical jig made of SUS304 (10 mmΦ, height 10 mm) was inserted as a negative electrode current collector from the bottom of a cylindrical tube jig made of polycarbonate (inner diameter 10 mmΦ, outer diameter 23 mmΦ, height 20 mm). Next, 80 mg of solid electrolyte (E-2) (3Li2S-P2S5-2LiI treated in a ball mill at 500 rpm for 10 hours) was inserted from the top of the cylindrical tube jig made of polycarbonate. Furthermore, a cylindrical jig made of SUS304 (10 mmΦ, height 15 mm) was inserted as a positive electrode current collector from the top of the cylindrical tube jig made of polycarbonate to sandwich the solid electrolyte (E-2) and press it at a pressure of 80 MPa for 3 minutes to form a solid electrolyte layer with a diameter of 10 mmΦ and a thickness of about 0.5 mm. Next, the SUS304 cylindrical jig (positive electrode current collector) inserted from above was removed, and 4.0 mg of the negative electrode composite was placed on top of the solid electrolyte layer inside the polycarbonate cylindrical tube. The SUS304 cylindrical jig (positive electrode current collector) was inserted from above again, and pressed at a pressure of 200 MPa for 3 minutes to form a negative electrode composite layer with a diameter of 10 mm and a thickness of approximately 0.05 mm. Next, the cylindrical jig (negative electrode current collector) made of SUS304 inserted from the bottom was removed, and a lithium sheet (manufactured by Honjo Metals Co., Ltd.) with a thickness of 0.20 mm was punched out to a diameter of 8 mmΦ as the negative electrode with a hole punch, and an indium sheet (manufactured by Furuuchi Chemical Co., Ltd.) with a thickness of 0.3 mm was punched out to a diameter of 9 mmΦ with a hole punch, which was then stacked and inserted from the bottom of a cylindrical tube jig made of polycarbonate, and a cylindrical jig (negative electrode current collector) made of SUS304 was inserted from the bottom again, and pressed for 3 minutes at a pressure of 80 MPa to form a lithium-indium alloy negative electrode. In this way, an all-solid-state lithium ion battery was produced in which, from the bottom, a negative electrode current collector, a lithium-indium alloy negative electrode, a solid electrolyte layer, a negative electrode composite layer, and a positive electrode current collector were stacked. This was sealed to form an evaluation battery.

[0140] (Si negative electrode half-cell preparation conditions 2: negative electrode composites 10-12, comparative negative electrode composite 3) In an argon gas atmosphere glove box, a cylindrical jig made of SKD11 (10 mmΦ, height 10 mm) was inserted as a negative electrode current collector from the bottom of a ceramic cylindrical tube jig (inner diameter 10 mmΦ, outer diameter 23 mmΦ, height 20 mm). Next, 80 mg of solid electrolyte (E-2) (3Li2S-P2S5-2LiI treated in a ball mill at 500 rpm for 10 hours) was inserted from the top of the ceramic cylindrical tube jig. Furthermore, a cylindrical jig made of SKD11 (10 mmΦ, height 15 mm) was inserted as a positive electrode current collector from the top of the ceramic cylindrical tube jig to sandwich the solid electrolyte (E-2) and press it at a pressure of 80 MPa for 3 minutes to form a solid electrolyte layer with a diameter of 10 mmΦ and a thickness of about 0.5 mm. Next, the cylindrical jig made of SKD11 (positive electrode current collector) that had been inserted from above was temporarily removed, and 5.0 mg of the negative electrode composite prepared was placed on top of the solid electrolyte layer inside the ceramic cylindrical tube. The cylindrical jig made of SKD11 (positive electrode current collector) was then inserted again from above and pressed at a pressure of 720 MPa for 3 minutes to form a negative electrode composite layer with a diameter of 10 mmΦ and a thickness of approximately 0.05 mm. Next, the cylindrical jig (negative electrode current collector) made of SKD11 inserted from the bottom was removed, and a lithium sheet (manufactured by Honjo Metals) with a thickness of 0.20 mm was punched out to a diameter of 8 mmΦ with a hole punch as a negative electrode, and an indium sheet (manufactured by Furuuchi Chemical Co., Ltd.) with a thickness of 0.3 mm was punched out to a diameter of 9 mmΦ with a hole punch, which were then stacked and inserted from the bottom of a ceramic cylindrical tube jig, and a cylindrical jig (negative electrode current collector) made of SKD11 was inserted from the bottom again, and pressed for 3 minutes at a pressure of 80 MPa to form a lithium-indium alloy negative electrode. In this way, an all-solid-state lithium ion battery was produced in which, from the bottom, a negative electrode current collector, a lithium-indium alloy negative electrode, a solid electrolyte layer, a negative electrode composite layer, and a positive electrode current collector were stacked. This was sealed to form an evaluation battery.

[0141] (Full Cell 1) In an argon gas atmosphere glove box, a cylindrical jig made of SUS304 (10 mmΦ, height 10 mm) was inserted as a negative electrode current collector from the bottom of a cylindrical tube jig made of polycarbonate (inner diameter 10 mmΦ, outer diameter 23 mmΦ, height 20 mm). Next, 80 mg of solid electrolyte (E-2) (3Li2S-P2S5-2LiI treated in a ball mill at 500 rpm for 10 hours) was inserted from the top of the cylindrical tube jig made of polycarbonate. Furthermore, a cylindrical jig made of SUS304 (10 mmΦ, height 15 mm) was inserted as a positive electrode current collector from the top of the cylindrical tube jig made of polycarbonate to sandwich the solid electrolyte (E-2) and press it at a pressure of 80 MPa for 3 minutes to form a solid electrolyte layer with a diameter of 10 mmΦ and a thickness of about 0.5 mm. Next, the SUS304 cylindrical jig (positive electrode current collector) inserted from above was removed once, and 7.5 mg of the positive electrode composite prepared was placed on the solid electrolyte layer in the polycarbonate cylindrical tube. The SUS304 cylindrical jig (positive electrode current collector) was inserted again from above and pressed at a pressure of 80 MPa for 3 minutes to form a positive electrode composite layer with a diameter of 10 mmΦ and a thickness of about 0.1 mm. Next, the SUS304 cylindrical jig (negative electrode current collector) inserted from below was removed, and 4.0 mg of the negative electrode composite was placed. Then, the SUS304 cylindrical jig (negative electrode current collector) was inserted again from below and pressed at a pressure of 200 MPa for 3 minutes to prepare an all-solid-state lithium-ion battery in which the negative electrode current collector, negative electrode composite layer, solid electrolyte layer, positive electrode composite layer, and positive electrode current collector were stacked in order from the bottom. This was sealed to prepare an evaluation battery.

[0142] (XRD measurement) Positive electrode composites 1-22, comparative positive electrode composites 1-4, negative electrode composites 1-12, and comparative negative electrode composites 1-3 were measured in the 2θ range of 10-60° using a SmartLab II manufactured by RIGAKU Corporation to obtain XRD spectra. Cases in which there was a peak other than the active material were marked as "present," and cases in which there was no peak other than the active material were marked as "absent." The results are shown in Tables 1 and 2.

[0143] (XPS measurement) Positive electrode composites 1 to 17, comparative positive electrode composites 1 and 2, negative electrode composites 1 to 9, and comparative negative electrode composites 1 and 2 were measured using a KRATOS Nova manufactured by KRATOS ANALYTICAL, Inc., to obtain XPS spectra. A peak was recorded as present in the vicinity of 165 eV, and no peak was recorded as absent. The results are shown in Tables 1 and 2. The "-" in the column for the presence or absence of an XPS peak near 165 eV indicates that no measurement was performed.

[0144] (DSC measurement) Measurements were performed on positive electrode composites 18 to 22, comparative positive electrode composites 3 and 4, negative electrode composites 10 to 12, and comparative negative electrode composite 3 using a comparative differential scanning calorimeter (DSC6200 manufactured by Seiko Instruments Inc.). The measurements were performed in the temperature range of 50°C to 500°C, with a heating rate of 5°C / min. The exothermic peaks of each composite are shown in Tables 1 and 2. Note that none of the solid electrolyte raw materials used in the production of each composite showed an exothermic peak in the temperature range of 50°C to 500°C. A "-" in the DSC exothermic peak temperature column indicates that no measurement was performed.

[0145] (Charge / discharge characteristic evaluation) The charging and discharging characteristics of the evaluation batteries prepared using the above positive electrode composites 1 to 22, comparative positive electrode composites 1 to 4, negative electrode composites 1 to 12, and comparative negative electrode composites 1 to 3 were evaluated using a charging and discharging device (ACD-M01A, manufactured by Aska Electronics Co., Ltd.). The positive electrode composites 1 to 17 and comparative positive electrode composites 1 to 2 were charged at a constant current-constant voltage of 0.2 mA at a voltage range of 0.5 V to 2.5 V and a current value of 0.2 mA at 25 ° C., and discharged at a constant current of 0.2 mA. The positive electrode composites 19 to 22 and comparative positive electrode composites 3 to 4 were charged at a constant current-constant voltage of 0.05 mA at a voltage range of 0.5 V to 2.5 V and a current value of 0.05 mA and discharged at a constant current of 0.05 mA at 45 ° C. The discharge capacity per weight of the positive electrode composite in the second cycle of each positive electrode composite was examined, and the results are shown in Table 1. Negative electrode composites 1-9 and comparative negative electrode composites 1-2 were discharged at a constant current of 0.2 mA at a voltage range of -0.6 V to 2.0 V and a current value of 0.2 mA at 25 ° C., and charged at a constant current of 0.2 mA. Negative electrode composites 10-12 and comparative negative electrode composite 3 were discharged at a constant current of 0.05 mA at a voltage range of -0.6 V to 2.0 V and a current value of 0.05 mA and charged at a constant current of 0.05 mA at 45 ° C. The charge capacity per weight of the negative electrode composite in the second cycle of each negative electrode composite was examined, and the results are shown in Table 2. Furthermore, full cell 1 was charged at a constant current-constant voltage of 0.0 V to 3.0 V and a current value of 0.2 mA at 25 ° C., and the discharge capacity per weight of the positive electrode composite in the second cycle of each full cell was examined, and the results are shown in Table 3. Here, for the half cells using the negative electrode composite and the comparative negative electrode composite, the upper limit of the discharge capacity per active material was limited to 2500 mAh / g.

[0146] [Table 1]

[0147] [Table 2]

[0148] [Table 3]

[0149] As shown in Tables 1 to 3, it was confirmed that the electrode assemblies (positive electrode assemblies and negative electrode assemblies) produced by the method for producing an electrode assembly for an all-solid-state lithium ion battery of the present invention had a solid electrolyte synthesized therein and were amorphous except for the positive electrode assemblies 21. Although the electrode assemblies (positive electrode assemblies and negative electrode assemblies) produced by the method for producing an electrode assembly for an all-solid-state lithium ion battery of the present invention were produced in one step, they showed high battery performance similar to that of the conventional production method (comparative positive electrode assemblies and comparative negative electrode assemblies). Usually, the production of a positive electrode or negative electrode assemblies consists of two steps, a step of producing a solid electrolyte and a step of producing a positive electrode or negative electrode assemblies, but the present invention allows production in one step, thereby improving productivity. [Industrial Applicability]

[0150] By using the manufacturing method of the present disclosure for an electrode composite for an all-solid-state lithium ion battery, an electrode composite can be manufactured with fewer steps than conventional methods, and therefore has high industrial applicability.

Claims

1. A method for producing an electrode composite for an all-solid-state lithium ion battery, comprising: An electrode active material; A solid electrolyte raw material; A carbon material which is a conductive material; The electrode composite material is compounded by mechanical energy to produce the electrode composite for an all-solid-state lithium ion battery, The specific surface area of ​​the carbon material is 1000 m 2 / g or more. A method for manufacturing an electrode composite for all-solid-state lithium-ion batteries.

2. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 1 , wherein the electrode active material is a positive electrode active material.

3. The positive electrode active material is a first Li 2 The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 2, wherein the total weight of the electrode composite for an all-solid-state lithium ion battery is 1.0 or more.

4. The solid electrolyte raw material is a second Li 2 S and P 2 S 5 The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 3, wherein the sulfide solid electrolyte raw material comprises:

5. In the electrode composite raw material, the first Li 2 S and the second Li 2 The sum of S and P 2 S 5 and the carbon material are in a weight ratio of 30 to 80:10 to 50:3 to 20. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 4.

6. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 4 or 5, wherein the electrode composite raw material further contains a lithium salt.

7. 7. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 6, wherein the lithium salt is at least one selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.

8. In the electrode composite raw material, the first Li 2 S and the second Li 2 The sum of S and the P 2 S 5 The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 6 or 7, wherein a weight ratio of the carbon material to the lithium salt is 30 to 80: 10 to 40: 3 to 20: 5 to 30.

9. 4. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 3, wherein the solid electrolyte raw material contains two or more selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.

10. In the electrode composite raw material, the first Li 2 The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 9, wherein a weight ratio of S, the solid electrolyte raw material, and the carbon material is 20 to 60: 20 to 70: 3 to 20.

11. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 1 , wherein the electrode active material is a negative electrode active material.

12. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 11, wherein the negative electrode active material is a Si-based active material comprising at least one of Si and a Si compound.

13. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 12, wherein the Si-based active material is Si.

14. The solid electrolyte raw material is Li 2 S and P 2 S 5 The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 12 or 13, wherein the sulfide solid electrolyte raw material comprises:

15. In the electrode composite raw material, the Si-based active material and Li 2 S and P 2 S 5 and the carbon material are in a weight ratio of 20 to 70: 10 to 30: 10 to 40: 3 to 20. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 14.

16. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 14 or 15, wherein the electrode composite raw material further contains a lithium salt.

17. 17. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 16, wherein the lithium salt is at least one selected from the group consisting of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.

18. In the electrode composite raw material, the Si-based active material and Li 2 S and P 2 S 5 The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 16 or 17, wherein a weight ratio of the carbon material to the lithium salt is 20 to 70: 10 to 30: 10 to 40: 3 to 20: 5 to 30.

19. 14. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 12 or 13, wherein the solid electrolyte raw material contains at least two of lithium oxide, lithium nitride, lithium fluoride, lithium chloride, lithium bromide, lithium iodide, lithium sulfate, lithium carbonate, lithium borate, lithium phosphate, lithium nitrate, lithium silicate, and lithium aluminate.

20. The method for producing an electrode composite for an all-solid-state lithium ion battery according to claim 19, wherein in the electrode composite raw material, a weight ratio of the Si-based active material, the solid electrolyte raw material, and the carbon material is 10 to 60: 20 to 80: 3 to 20.

Citation Information

Patent Citations

  • Electrode material manufacturing method, and electrode material

    JP2013098024A

  • Positive electrode mixture

    JP2014011033A

  • Positive electrode composite and manufacturing method thereof

    JP2019212447A

  • All-solid battery and manufacturing method thereof

    JP2020021674A

  • All-solid battery, and manufacturing method thereof

    JP2020064701A